Erfaringer med å være pårørende når en nærstående er døende - Solvoll, Betty-Ann (Nordisk Tidsskrift for Helseforskning, 2016)
Relatives’ experiences during the dying process of a loved one The purpose of this essay is to explore the relatives’ experiences of being with their loved ones during the dying process. Research question: How do relatives experience being with their loved ones during the dying process? Within a phenomenological hermeneutical framework the personal experiences of the author are interpreted. Essay as a method of critical investigation is used. Relatives may experience the situation strongly existential, being stuck in dilemmas, thus making them less responsive to the actions of the nurses. This challenges nurses to be aware and to put efforts in trying to understand the other and develop their ability to be sensitive and receptive. Whoever is silent, will hear. Being attentive to silence may be a useful approach in order to being emotionally present to the other.